Contraceptive use among people living with HIV and AIDS from selected communities in Siteki, Eswatini - Thwala, Ncamsile; Fernandes, Lucy; Oguntibeju, Oluwafemi Omoniyi (International Journal of Innovative Research and Scientific Studies, 2023)
Eswatini is among the countries with the highest prevalence of Human Immunodeficiency Virus (HIV) infection and Acquired Immunodeficiency Syndrome (AIDS) with a prevalence of 26% among sexually active adults. Strong reproductive health services including the use and provision of contraceptives are necessary to improve sexual health especially with HIV and AIDS (PLWHA). The study aimed to determine the socio-demographic characteristics, the preferred types of contraceptives, experiences with contraceptive use and the factors that influenced access to contraceptives for PLWHA in the selected communities. This quantitative survey used a structured, self-administered questionnaire to collect data from PLWHA aged 21-49 who are registered in support groups with the Swaziland AIDS Support Organization (SASO). The findings revealed that 82.3% of the respondents were using contraceptives and among these 69% were using barrier methods that could prevent both pregnancy and HIV infection. There were 11% of the respondents who did not desire to have children but were not using contraceptives. Generally, knowledge of contraceptive use was high and all the respondents knew that they must use condoms or dual methods to ensure safer sex and the prevention of a pregnancy. The findings of this study should assist health promoters in designing and implementing interventions that would address the barriers to contraceptive use among PLWHA.